An analysis on the risk of being injured and killed in road travel injuries in Namibia. Issue 2 (3rd April 2021) - Chatukuta, Mitchel; Groce, Nora; Mindel, Jenny; Kett, Maria
Abstract: Road traffic injuries (RTIs) are a major, global problem. Few studies on RTIs have been conducted in Namibia, despite having one of the highest RTI rates globally. We conducted multinomial logistic regression on national Namibian datasets on RTIs 2012–2014. Being a motorcyclist was associated with the greatest risk of being injured (adjusted Relative Risk Ratio (aRRR) 82.1 (95% CI 47.2–142.9)) or killed (aRRR 202.1 (112.7–362.7)). Risks were also elevated for cyclists (57.3 (23.6–139.5)), pedestrians (15.8 (13.2–18.9), passengers (6.1 (5.2–7.2)), relative to drivers. Among those admitted to hospital, the method of transportation to hospital had the largest association with the risk of dying. To our knowledge this study presents new information on vulnerability of different road users, which can be of use to policymakers to develop specific and targeted interventions to protect the most vulnerable road users.